Immunomodulatory, Antioxidant, and Prophylactic Effects of the COA Plus Mixture in Plasmodium Berghei Infected Mice - Lomo-Mainoo, D.N. L. (University of Ghana, 2024)
The COA Plus mixture, an enhanced formulation of the original COA mixture developed by COA Research and Manufacturing Ltd in 2024, is registered by the Food and Drug Authority as an immune booster. While existing studies support the efficacy of the original COA mixture, data on COA Plus are lacking. This study assessed its immunological, antioxidant, and prophylactic potential in female ICR mice. Thirty-five mice were divided into five groups: Normal Control, Parasite Control (infected with Plasmodium berghei, Parasite+ Doxycycline, Parasite + COA, and COA only. The Normal Control and Parasite Control groups were administered distilled water for 8 weeks, with the Parasite Control group inoculated with P. berghei after this period. The Parasite + Doxycycline group received doxycycline (0.5 mg/kg) prior to parasite inoculation, while the COA groups were treated with COA Plus (0.30 ml/kg) for 8 weeks, with parasite inoculation after the 8th week for the COA + Parasite group. Blood samples were collected for cytokine profiling, parasitemia monitoring, and hematological analysis. Organs were harvested, and liver was used for lipid peroxidation assessment. The COA-only group showed reduced IL-4 levels suggesting positive immunomodulatory effects. Elevated IL-10 levels in the COA-only group indicated an enhanced inflammatory response, while high IFN- γ levels in the COA + Parasite group reflected a strengthened Th1 response, critical for malaria control. The COA + Parasite group also exhibited a reduction in parasitemia, reaching nearly 0% within 72 hours, demonstrating COA Plus Mixture’s prophylactic potential. Both the COA and Doxycycline groups had elevated malonyl dialdehyde (MDA) levels, indicating oxidative stress, yet COA likely triggered both pro-oxidant and antioxidant responses, promoting immune resilience. COA treatment enhanced platelets count, confirming its immune-signaling (cytokines and chemokines) effects. In conclusion, the COA Plus Mixture exhibited significant immunomodulatory, antioxidant, and prophylactic effects against P. berghei infection, validating the purported claim of its use as a therapeutic agent for malaria prevention and immune support.
MPhil. Applied Parasitology
Keywords: COA Plus mixture; Food and Drug Authority; Parasite+ Doxycycline